Teaching, learning and assessment during covid-19: challenges and prospects of the University of Ibadan ert (2023)
The Covid-19 pandemic has brought extraordinary challenges and has affected the educational sectors in all ramifications. This, therefore calls for the need to sustain and provide quality education despite its challenges and forced many institutions to reposition their educational practices which predominantly adopted the conventional methods of teaching and learning, as well as assessment which was on venue-based and restricted in terms of online accessibility, swiftness, assessment and materials interaction. In the new normal period, there is much emphasize to reposition our institutions for teaching and learning in terms of the mode of instruction and assessment. Many countries, Nigeria inclusive were forced to migrate to a more robust innovative online teaching and learning, and different forms of online instruction and assessment using diverse platforms such as Emergence Remote Teaching (ERT), google meet, zoom, Microsoft team and others. These online teaching platforms have implications for lecturer-student interaction, satisfaction, engagement, and success in curriculum planning and implementation issues. Seventy-five lecturers in the faculty of Education from the 11 departments partake in the study. Questionnaires and structured interviews were used to collect data. Data collected were analyzed using the descriptive statistics of mean, while the qualitative data was content analyzed. This study identified the challenges of teaching staff and students in teaching and learning using ERT, University of Ibadan as a case study. Challenges idented includes: internet connectivity, technological experiences, power supply,and lack of access to reliable internet connection .The perceived benefitswere a reduction in transportation costs, effective distance learning, stability in communication and lecturers' familiarisation with online emerging technology. ERT platforms should be designed with engaging and interactive content, instructors and students' learning activities to maintain students’ interest during the lesson session were recommended.